Hepatoprotective phenylethanoid glycosides from Cirsium setosum. Issue 16 (17th August 2016) - Ma, Qinge; Guo, Yongming; Luo, Baomin; Liu, Wenmin; Wei, Rongrui; Yang, Chunxia; Ding, Chenghua; Xu, Xuefeng; He, Minghui
Abstract: Two new phenylethanoid glycosides, namely β -D-glucopyranoside, 1″- O -(7 S )-7-(3-methoxyl-4-hydroxyphenyl)-7-methoxyethyl-3″- α -L-rhamnopyranosyl-4″-[(8 E )-7-(3-methoxyl-4-hydroxyphenyl)-8-propenoate] (1 ) and β -D-glucopyranoside, 1″- O -(7 S )-7-(3-methoxyl-4-hydroxyphenyl)-7-methoxyethyl-3″- α -L-rhamnopyranosyl-4″-[(8 E )-7-(4-hydroxyphenyl)-8-propenoate] (2 ), together with six phenylethanoid glycosides were isolated from Cirsium setosum . Their structures were elucidated by their spectroscopic data and references. Compounds2, 4, 5, 7 and8 (10 μM) exhibited moderate hepatoprotective activities. Compounds (3–8 ) were obtained from this plant for the first time. Abstract :